The Relationship Between the Role of Agricultural Extension Workers and Farmers’ Technology Adoption in Increasing Rice Production at the Agricultural Extension Center of Samaturu District, Kolaka Regency - Rina Astarika (Indonesian Journal of Multidisciplinary Scientific Studies, 2026)
Efforts to increase rice production have so far remained focused on major production centers, while villages with potential paddy fields supported by technical, semi-technical, or simple irrigation systems have not been fully empowered. In Samaturu District, agricultural extension workers—both Civil Servants and Daily Freelance Agricultural Extension Support Personnel (THL–TBPP)—face institutional constraints because rice production improvement programs are still dominated by the Kolaka Regency Agriculture Service. This study aims to: (1) analyze the relationship between the role of extension workers and increased rice production, (2) analyze the relationship between farmers’ technology adoption and increased rice production, and (3) examine the simultaneous effect of the role of extension workers and technology adoption on increased rice production. The study was conducted from January to May 2025 in the administrative area of Samaturu District. The study population consisted of rice farmers who had been farming for at least two years, with a sample of 30 farmers selected using snowball sampling. The variables examined were the role of extension workers (X1), technology adoption (X2), and increased rice production (Y). The data were analyzed using correlation and regression tests. The results showed that the role of extension workers did not contribute significantly to increased rice production, while technology adoption also had no significant effect. However, simultaneously, the two variables demonstrated a synergistic relationship that could jointly support increased rice production.